Repeated monitoring of blood parameters for evaluating strain and overload in elite football players: is it justified? - Meister, S.; aus der Fünten, K.; Meyer, T. (Journal of Sports Sciences, 2014)
Repeated determination of a panel of routine laboratory parameters might sound reasonable for screening purposes in elite athletes. However, from the existing literature, frequent blood sampling does not contribute to an appropriate monitoring of high physical strain and overload in elite football players. The use of an intraindividual profile of an elite player including known baseline levels which have been repeatedly measured might be a more convincing approach. In line with Fallon (2008), on clinical grounds a repeated wide routine biochemical screening (without suspicious complaints or signs) cannot be recommended.